Effect of nanostructure on thermoelectric properties of La0.7Sr0.3MnO3 in 300–600 K temperature range. (16th May 2018) - Singh, Saurabh; Srivastav, Simant Kumar; Patel, Ashutosh; Chatterjee, Ratnamala; Pandey, Sudhir K
Abstract: In oxide materials, nanostructuring effect has been found a very promising approach for the enhancement of figure-of-merit, ZT . In the present work, we have synthesized La0.7 Sr0.3 MnO3 (LSMO) compound using sol-gel method and samples of crystallite size of ∼20, ∼41, and ∼49 nm were obtained by giving different heat treatment. Seebeck coefficient ( α ), electrical resistivity ( ρ ), and thermal conductivity ( κ ) measurements were carried out in 300–600 K temperature range. The systematic change in the values of α from ∼−19 μ V/K to ∼−24 μ V/K and drastic reduction in the values of κ from ∼0.88 W/mK to ∼0.23 W/mK are observed as crystallite size is reduced from 49 nm to 20 nm at ∼600 K. Also, fall in the values of ρ in the paramagnetic (PM) insulator phase (400–600 K) are effectively responsible for the increasing trend in the values of ZT at high temperature. For the crystallite size of 41 nm, the value of ZT at 600 K was found to be ∼0.017.